Using Semi-Analytic Method to Decreasing Dangers of Lead - Tawfiq, L. N. M.; Tawfiq, M. N. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The aim of this paper is to present a method for solving of system of first order initial value problems of ordinary differential equation by a semi-analytic technique with constructing polynomial solutions for decreasing dangers of lead. The original problem is concerned using two-point osculatory interpolation with the fit equals  numbers of derivatives at the end points of an interval [0 , 1].